ADVERTISING CREATIVITY DAN PRODUCT QUALITY: UPAYA MENGOPTIMALISASI PURCHASE DECISION - Noviani, Lona; Nabella, Ratih Intania; Rifai, achmad (Universitas Banten Jaya, 2023)
Companies need to pay attention to advertising creativity and product quality in order to improve consumer purchasing decisions. This study aims to examine the effect of advertising creativity and product quality on purchase decisions. This study used a quantitative method with a sample taken of 80 respondents using sunsilk shampoo in Serang City using the purposive sampling method. Data analysis uses the SEM approach which is processed through SmartPLS. The results test show that advertising creativity has a positive and significant direct effect on purchase decisions. Product quality has a positive and significant direct effect on purchase decision. This study concludes that advertising creativity has the most dominant effect on purchase decisions.